Trade Liberalization, Foreign Investment and Economic Growth: Experience from Non-Oil Producing Countries in Africa - Logan, Chine Sp.; Manasseh, Charles O.; Ede, Kenechukwu K. (International Journal of Economics and Financial Issues, 2024)
This study focuses on trade liberalization, foreign investment and economic growth in non-oil-producing countries of Africa using the panel autoregressive distributed lag (ARDL) model. Annual time series data spanning from 2000 to 2023. The study reveals a strong long-term relationship between trade liberalization, foreign direct investment (FDI), and economic growth in non-oil-producing African countries. This finding is evidenced by the rejection of the “no long-run relationship” hypothesis, indicating a solid and enduring connection among these factors, which aligns with previous research. Most variables conform to theoretical expectations, supporting the hypothesis that trade liberalization and FDI contribute positively to economic growth. However, FDI and exchange rates exhibit unexpected deviations, likely reflecting structural challenges common in non-oil African economies, such as barriers that limit stable FDI inflows and hinder sustainable growth. The error correction term (ECT) further suggests that these economies adjust quickly from deviations, with respective short-run adjustment rates of 90%, 10%, and 50% in different model specifications. This high responsiveness indicates that, despite short-term disruptions, these economies tend to revert swiftly to their long-term growth trajectories. Based on the findings, we recommend that policies should be directed towards the pursuit of consistent and sustainable trade liberalization by reducing trade barriers, and reduction of obstacles to foreign investment to improve economic growth in non-oil-producing countries of Africa.